1999
DOI: 10.1159/000054504
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Endocrine Responses to Psychosocial Stress and Dexamethasone/ Corticotropin-Releasing Hormone in Healthy Postmenopausal Women and Young Controls: The Impact of Age and a Two-Week Estradiol Treatment

Abstract: In this placebo-controlled double-blind study, psychological and endocrine stress responses were investigated in healthy postmenopausal placebo-treated women (n = 15; 60–75 years; placebo via transdermal patches), healthy postmenopausal estradiol-treated women (n = 13; 60–79 years; 0.1 mg 17β-estradiol daily via transdermal patches) and young controls (n = 15; 20–31 years; untreated). The aged subjects received estradiol or placebo treatment for 14 days. All subjects were then exposed to the ‘Trier Social Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 33 publications
5
65
3
1
Order By: Relevance
“…32 Furthermore, oral contraceptives profoundly decrease the free cortisol response to this stressor. 33 We have similar data confirming large menstrual cycle difference in free (saliva) cortisol response to the TSST in normal women, as well as a markedly blunted response in oral contraceptive users (Young, unpublished data).…”
Section: Sex Differences In Stress Systemssupporting
confidence: 76%
See 1 more Smart Citation
“…32 Furthermore, oral contraceptives profoundly decrease the free cortisol response to this stressor. 33 We have similar data confirming large menstrual cycle difference in free (saliva) cortisol response to the TSST in normal women, as well as a markedly blunted response in oral contraceptive users (Young, unpublished data).…”
Section: Sex Differences In Stress Systemssupporting
confidence: 76%
“…41 Estradiol administered to postmenopausal women had no effect on the response to the stressor, TSST, but it did decrease the response to the dex-CRH challenge. 33 In a clever study design in normally menstruating women, Roca et al 42,43 analyzed women treated with Lupron, which leads to a loss of all gonadal steroids, followed by estradiol or progesterone add-back phases. They examined the response to exercise stress and found that the exercise stress response was increased during the progesterone 'add-back' phase but not during the estrogen 'add-back' phase.…”
Section: Which Ovarian Steroids Influence the Hpa Axis?mentioning
confidence: 99%
“…In line with this, Kudielka et al (1999) found that healthy elderly women (60-75 years) exhibited a markedly enhanced cortisol response to the DEX/CRH test compared to young controls (20-31 years). In contrast, a more recent study found no significant effect of age on hormonal responses to the DEX/ CRH test in acutely depressed inpatients (Kunzel et al, 2003).…”
Section: Effects Of Age and Gendersupporting
confidence: 66%
“…Komesaroff et al (1999) found that 8 weeks of E2 supplementation produce a similar reduction of physiological responses to mental stress. In a low dose, short duration transdermal estrogen study in PMW, the TSST was not found to provoke a differential effect on physiological measures in estrogentreated women (Kudielka et al, 1999). In an extensive review, Kajantie and Phillips (2006) conclude that there is an increase in sympathoadrenal responsiveness after menopause which is attenuated during oral hormone therapy and that sex differences in sympathoadrenal responses are likely the result of estrogen.…”
Section: Stress Sensitivity Of Pmwmentioning
confidence: 96%
“…Prior studies of the effects of hormone treatment in PMW on experimentally induced psychological or psychosocial stress have generally focused on physiological reactivity such as blood pressure and hormonal responses (Burleson et al, 1998;Ceresini et al, 2000;Komesaroff et al, 1999;Kudielka et al, 1999;Lindheim et al, 1992b;Matthews et al, 2005). However, there has not been an experimental study that has focused on the effects of estrogen treatment in PMW on mood reactivity to psychosocial stress and examining whether hormonal effects interact with levels of brain monoamine neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%